GOVERNABILITY IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR NEGERI 18 PEKANBARU TAHUN 2013-2015 - Syed Agung Afandi; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Education is a means of educating the nation. Through the education of every citizen is able to maximize the potential establish a life and advance civilization. School-Based Management in an effort decentralized management of education in Indonesia is expected to improve the quality of education on an ongoing basis. The purpose of this study was to know the governability in the implementation of school-based management in Elementary School 18 Pekanbaru. This study uses the theory Sutoro Eko with qualitative approach and descriptive methods. This research was conducted through observation, interviews and documentation. Data analysis technique is done by means of data reduction, data presentation and conclusion and triangulation techniques. The results of this study indicate that the managerial capacity of the principal that the Management of the planning and evaluation of programs, curriculum, teaching and learning, workforce, equipment and supplies, finance, student services, relationship between the school and community and school climate have been going well, but the principal must increased its performance on manjemen workforce, equipment and supplies, school finance and school and community relationship management. While the political capacity, the principal has been able to gain political legitimacy to exercise its authority. The school principal has the capability responsive, regulatory and symbolic good.Keywords: Governability, School-Based Management